COVID-19 Lockdowns and Childbirth Delivery Care in India - Sandipa Bhattacharjee; Shamma Adeeb Alam; Bijetri Bose (Global Labor Organization (GLO), 2025)
Background: Government-imposed lockdowns during the COVID-19 pandemic disrupted essential healthcare services in low- and middle-income countries (LMICs), including childbirth delivery care. While a few studies have documented a decline in institutional deliveries, little is known about the effects on skilled birth attendance, facility-type differences, and underlying mechanisms of disruption. Methods: We examine the impact of lockdowns in India on institutional deliveries, skilled birth attendance, and delivery care across public and private facilities. We compare pre-, during, and post-lockdown periods using logistic regression to isolate the specific effects of lockdowns from broader pandemic-related disruptions. We also analyze potential mechanisms, including transportation barriers, facility closures, treatment costs, perceived quality of care and other reasons. Findings: Our findings suggest that institutional deliveries and skilled birth attendance declined during and after the lockdown compared to the pre-pandemic period. Births in private facilities also decreased during the lockdown but showed no significant change post-lockdown relative to pre-lockdown levels. Out-of-pocket expenditures increased in private facilities during the lockdown, potentially limiting access. No significant differences were observed in reported barriers to institutional delivery, such as transportation unavailability, facility closures, distrust in health services, or cultural factors. However, fewer women cited economic constraints as a reason for non-institutional delivery during the lockdown, while reports of "other reasons" increased during and after the lockdown. Interpretation: Our results show that lockdowns exacerbated barriers to skilled delivery care in India, worsening healthcare inequalities. The rising costs in private facilities added another challenge, pushing care out of reach for many. Ensuring affordable maternal healthcare is crucial highlighting the need for policies that sustain maternal health services during crises and safeguard vulnerable populations.
Keywords: I12; I18; J13; 330; COVID-19; lockdown; delivery care